Kinerja bom kalorimeter sebagai alat ukur nilai kalor bahan bakar - Mafruddin Mafruddin; Sulis Dri Handono; Mustofa Mustofa; Eko Mujianto; Ramadan Saputra (TURBO [Tulisan Riset Berbasis Online], 2022)
The calorific value contained in the fuel is one of the benchmarks for the quality of the fuel. To test the calorific value of fuel, a test device such as a bomb calorimeter is needed. The performance of the calorimeter bomb is influenced by the heat absorbed by the water media and the heat wasted into the environment and the heat from the combustion that occurs in the combustion chamber (reactor). Combustion in a bomb calorimeter is affected by the rate of air flow used. The wasted heat to the environment can be minimized by using an insulator on the outer wall of the calorimeter bomb. The purpose of this study was to determine the effect of air flow rate and type of insulator on combustion temperature, heat transfer and accuracy of bomb calorimeter test results. The method used in this research is experimental research by making and testing bomb calorimeters using variations in the air flow rate in the combustion process, namely 40 m/s, 50 m/s and 60 m/s and the types of insulators are air and Fiber glass wool. From the results of the research that has been done, it can be concluded that the air flow rate and the type of insulator affect the combustion temperature, heat transfer and accuracy of the bomb calorimeter. The maximum combustion temperature is 480 °C to 490 °C, heat transfer is 77.7 watts and the highest bomb calorimeter accuracy is 98% obtained at variations in air flow rate of 60 m/s and Fiber glass wool insulator.